Pembuatan TTG (Teknologi Tepat Guna) Rak Tanaman Di Desa Kebondalem, Kecamatan Bareng, Kabupaten Jombang (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2023)
Production and counseling activities for Appropriate Technology (TTG) Thematic KKN 03 MBKM students made Appropriate Technology (TTG) Plant Shelves aimed at the surrounding community. Appropriate Technology (TTG) This Plant Shelf contains vegetable plants that are easy to care for and are often used by the local community, especially mothers. The plant contains vegetable plants in the form of chilies, eggplants and tomatoes. MBKM Thematic KKN 03 students succeeded in making 1 shelf containing 16 plants with the hope that these plants would make things easier for the local community. After the Appropriate Technology (TTG) Plant Racks became Thematic KKN 03 MBKM students conducted counseling to the surrounding community, especially PKK mothers regarding the benefits and how to care for Appropriate Technology (TTG) Plant Shelves so that they last a long time so that they will continue to provide benefits to the surrounding community in Kebondalem Village, Bareng District, Jombang Regency.